Green Intellectual Capital and Firm Value: Evidence from Green Human, Structural and Relational Capital in Indonesian Manufacturing Companies - Nico Alexander; Ariesta Tika K.P.S. Putri; Ade Hanifa Putri (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2026)
Sustainability has become a key objective for companies, encouraging environmentally friendly innovations through the development of green intellectual capital. In accordance with the resource-based view and stakeholder theories, effective management of green intellectual capital can enhance firm value by utilizing resources for stakeholders’ benefit. This research aims to provide empirical evidence on the effect of green intellectual capital on firm value. As its novelty, this study examines each component of green intellectual capital individually to identify which component contributes to firm value. The sample comprised 162 manufacturing companies listed on the Indonesia Stock Exchange during 2022–2024 by using purposive sampling. The results indicate that green intellectual capital increases firm value, with green relational capital being the primary contributor. This is because companies engage stakeholders to ensure sustainability, leading to a positive perception of the company and consequently driving an increase in corporate value. These findings provide a theoretical basis for companies to develop sustainability-supporting resources, particularly by maintaining relationships and collaborating with stakeholders to achieve their sustainability objectives.